A Turbidity Test Based Centrifugal Microfluidics Diagnostic System for Simultaneous Detection of HBV, HCV, and CMV. (5th July 2015) - Chang, Hung-Cheng; Chao, Yu-Tin; Yen, Jia-Yush; Yu, Ya-Lin; Lee, Chun-Nan; Ho, Bing-Ching; Liu, Kou-Chen; Fang, Jiunn; Lin, Chii-Wann; Lee, Jiun-Haw
Abstract : This paper presents a LAMP- (loop-mediated isothermal amplification-) based lab-on-disk optical system that allows the simultaneous detection of hepatitis B virus, hepatitis C virus, and cytomegalovirus. The various flow stages are controlled in the proposed system using different balance among centrifugal pumping, Coriolis pumping, and the capillary force. We have implemented a servo system for positioning and speed control for the heating and centrifugal pumping. We have also successfully employed a polymer light-emitting diode section for turbidity detection. The easy-to-use one-click system can perform diagnostics in less than 1 hour.